Ensuring Fairness in Automated Traffic Enforcement: Examining Algorithmic Justice and Due Process in Malang's ETLE System - Angka Husada; Budi Parmono; Rahmatul Hidayati (Bulletin of Community Engagement, 2026)
This study analyzes the implementation of Electronic Traffic Law Enforcement (ETLE) in Indonesia and its consequential due process principle and algorithmic justice. The use of electronic traffic law enforcement (ETLE) has been embraced as a means to better achieve efficiency, transparency, and objectivity in the enforcement of traffic laws; however, procedural tension continues regarding how this style of enforcement plays into issues of due process and individual rights. This scientific paper aims to conduct a critical review on whether the ETLE system in Malang Regency aligns with due process of law and algorithmic justice. This study uses an empirical juridical (socio-legal) method with a descriptive-analytical approach, which makes legal analysis and field data from interviews, observations, and official traffic violations from the years 2021–2024. Results based on data until October 2023 show that ETLE enhances administrative efficiency, minimizes officer-citizen interaction, and solidifies evidence-based enforcement. Nonetheless, the system does not adequately satisfy due process and falls short—notably with regard to the right to be informed, the right to be heard, and access to effective remedies. Moreover, lack of transparency and accountability and inadequate human oversight are gaps in reaching algorithmic justice. ETLE increases governance quality but requires a robust mechanism for institutional and procedural reforms to augment fairness and transparency in the detection, prosecution, and adjudication of offenders while ensuring the protection of fundamental legal rights.